New considerations around the Language and Literature class in pre-university - Machín Hernández, Karina; García Escobio, Marialina Ana; Martínez Bencomo, Haydee Elena (The Educational Journal of Works Aimed at the XXI century (XXI CHALLENGES), 2023)
This article addresses the main research results about the updating of didactic about and pedagogical knowledge in the teaching of the subject Literature and Language in pre-university. Emphasis is placed on explaining the results emanating from the research Project actions for the improvement of the learning of language and literature in secondary education in the province of Pinar del Río. Based on this, an explanation is made of the main theories that contemplate an update of the teaching-learning process of the Third improvement and the results obtained from the implementation of the conceived didactic actions are explained.